Evaluation of Role Played by Mediators of Immediate Hypersensitivity in Exercise-induced Asthma - E. C. Deal; Stephen I. Wasserman; Nicholas A. Soter; R. H. Ingram; E. R. McFadden (1980)
To determine whether mediators of immediate hypersensitivity played a role in the pathogenesis of exercise-induced asthma, we measured the concentration of histamine and neutrophil-chemotactic activity present in systemic arterial blood during thermal challenges in five asymptomatic asthmatics. Because exercise-induced asthma has been shown to be a result of respiratory heat loss and because respiratory heat loss during isocapnic hyperventilation has been shown to give identical responses, we chose the latter provocational method in order to minimize increases in cardiac output that might interfere with the interpretation of mediator concentrations in arterial blood. Multiple aspects of pulmonary mechanics were also recorded before and after provocation. The results of these studies were then compared with the effects observed when the same subjects inhaled aerosols of specific antigens on the same day. Each challenge produced identical alterations in lung function, and neither was associated with consistent changes in arterial histamine. However, antigen provocation evoked a sustained and prolonged release of neutrophil chemotactic activity in each subject, whereas isocapnic hyperventilation with cold air was without effect. These data strongly suggest that mast-cell derived mediators are not involved in the development or maintenance of the bronchial obstruction that follows exercise in asthmatics.